Investigating The Long-Term Effects Of Small-Scale Pedagogical Interventions On Student Motivation And Engagement Tracking Small-Scale Pedagogical Motivation - Zainab khan (PhD Scholar) , Dr. Muniza Malik , Dr. Lubna Ahmed Soomro , Dawar Awan , Dr. Shiraz Khan , Dr. Athar Marwat , Fahad Asghar (Migration Letters, 2024)
Social determination theory was used to analyse small-scale educational interventions for student motivation. SDT holds that people have psychological needs for autonomy, competence, and relatedness. These demands are essential for intrinsic motivation and good functioning. The study examines how these pedagogical initiatives affect students’ long-term motivation and engagement, prompting examination of SDT principles including autonomy, competence, and relatedness. They also noted that student expectations shape their university career. Studies increasingly emphasise the instructional role in student motivation and engagement. Multisource, three-wave da[1]ta with two-month delays from varied students show that small-scale pedagogy motivates and engages pupils. We studied mediation impact in Amos using Bootstrap. Qualification and gender are controls. Student expectations can mediate learning mechanisms during instructional practises and motivate and engage students. These data suggest unique instructional pedagogical strategies are needed to motivate and engage students. Effective teaching methods can raise academic standards by motivating and engaging pupils. The study can improve teaching by using online resources, simulations, virtual laboratories, and interactive platforms. Teachers and schools can create an environment where kids are motivated, engaged, and academically ready.